Information Disclosure in Sales - Holley, David M. (Journal of business ethics, 1998)
Moral intuitions vary with regard to how much information a salesperson needs to disclose to a potential buyer. Through an analysis of the social role of salesperson and ethical argument, it is established that there is a general obligation to disclose what a buyer would need to make a reasonable judgment about whether to purchase the product. This rule is interpreted and shown to be superior to alternatives when appropriately qualified.